Praktik Hybrid Waris Dalam Pembagian Warisan Keluarga di Desa Kelutan Kecamatan Ngronggot Kabupaten Nganjuk - Roudlotul Jannatil Firdaus; Nizam Fauzida (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2026)
Indonesia's pluralistic legal system has given rise to various inheritance distribution practices that combine Islamic inheritance law and customary law. This study aims to examine the forms of hybrid inheritance practices in Kelutan Village, Ngronggot District, Nganjuk Regency, and to identify the factors encouraging the integration of Islamic and customary inheritance principles. This research employed a qualitative method with an empirical approach. Data were collected through observation, interviews, and documentation, and analyzed descriptively using the perspectives of Islamic inheritance law, customary law, and maqāṣid al-sharīʿah. The findings reveal three inheritance distribution models practiced by the community: distribution based entirely on Islamic inheritance law (farā'iḍ), distribution based on customary law through the akad rukun mechanism, and a hybrid model combining both systems. The hybrid model is the most widely practiced. In this model, inheritance is first distributed according to farā'iḍ, after which male heirs voluntarily transfer part of their shares to female heirs through akad rukun to preserve family harmony and achieve a socially accepted sense of justice. This practice reflects legal adaptation within Indonesia's pluralistic legal system by accommodating religious obligations alongside local customary values, provided that the redistribution remains voluntary and continues to uphold the principles of justice, public benefit, and family harmony.